Effects of Food Concentration and Photoperiod on Egg Production, Female Life Expectancy and Population Dynamics of the Paracalanid Copepod, Bestiolina amoyensis - Wang, Lin; Wang, Shuhong; Zeng, Chaoshu; Wang, Yuyue; Zeng, Chunxiao (Frontiers in Marine Science, 2021)
The paracalanid copepod, Bestiolina amoyensis, is a widely distributed species occurring in subtropical inshore waters across the Pacific Ocean. Its small size, herbivorous feeding habit, and high adaptability make the species one of the most promising candidates as potential live feed for hatchery larval rearing. This study investigated effects of different feeding density of microalgae Isochrysis spp. (1 × 105, 2 × 105, 3 × 105, 4 × 105, and 5 × 105 cells ml–1) and photoperiod (8L:16D, 12L:12D, and 16L:8D) on productivity-related parameters, including egg production, female life expectancy and population dynamics of B. amoyensis. Results showed that total egg output over female lifespan, final population size and intrinsic rate of population of 12L:12D photoperiod treatments were always the highest among three photoperiod conditions, especially at the food concentration of 4 × 105 cells ml–1, indicating B. amoyensis had high reproductive performance and the population was in a more stable status. The number of nauplii from 4 × 105 cells ml–1 algal concentration treatment accounted for 75% of the population, and the ratio of females to males approaching 1:1 when photoperiod was 12L:12D; female life expectancy was 10.5 ± 0.6 days. In conclusion, our results showed that Isochrysis spp. is a suitable feed for B. amoyensis with an optimal concentration at 4 × 105 cells mL–1; the optimal photoperiod for B. amoyensis rearing is 12L:12D. The relatively long reproductive lifespan and high intrinsic population increase rate make B. amoyensis a good candidate to develop culture techniques for hatchery larval rearing.